Mesenchymal stem cells-derived exosomes ameliorate blue light stimulation in retinal pigment epithelium cells and retinal laser injury by VEGF-dependent mechanism - Guang-Hui He; Wei Zhang; Ying-Xue Ma; Jing Yang; Li Chen; Jian Song; Song Chen (International Journal of Ophthalmology, 2018)
AIM: To observe the effect of exosomes derived from human umbilical cord blood mesenchymal stem cells (hUCMSCs) on the expression of vascular endothelial growth factor-A (VEGF-A) in blue light injured human retinal pigment epithelial (RPE) cells and laser-induced choroidal neovascularization (CNV) in rats. METHODS: Exosomes were isolated from hUCMSCs and characterized by transmission electron microscope and Western blot. MSCs-derived exosomes were cultured with RPE cells exposed to blue light. The mRNA and protein expression of VEGF-A were determined by real time-polymerase chain reaction (PCR) and Western blot, respectively. Immunofluorescence assay was used for the detection of the expression level of VEGF-A. We injected different doses of MSCs-derived exosomes intravitreally to observe and compare their effects in a mouse model of laser-induced retinal injury. The histological structure of CNV in rats was inspected by hematoxylin-eosin (HE) staining and fundus fluorescein angiography. The expression of VEGF-A was detected by immunohistochemistry. RESULTS: Exosomes exhibited the typical characteristic morphology (cup-shaped) and size (diameter between 50 and 150 nm). The exosomes marker, CD63, and hUCMSCs marker, CD90, showed a robust presence. In vitro, MSCs-derived exosomes downregulated the mRNA(Exo-L: t=6.485, 7.959, 9.286; Exo-M: t=7.517, 10.170, 13.413; Exo-H: t=10.317, 12.234, 14.592, P<0.05) and protein (Exo-L: t=2.945, 4.477, 6.657; Exo-M: t=4.713, 6.421, 8.836; Exo-H: t=6.539, 12.194, 12.783; P<0.05) expression of VEGF-A in RPE cells after blue light stimulation. In vivo, we found that the MSCs-derived exosomes reduced damage, distinctly downregulated VEGF-A (Exo-H: t=0.957, 1.382; P<0.05), and gradually improved the histological structures of CNV for a better visual function (Exo-L: 0.346, Exo-M: 3.382, Exo-H: 8.571; P<0.05). CONCLUSION: MSCs-derived exosomes ameliorate blue light stimulation in RPE cells and laser-induced retinal injury via downregulation of VEGF-A.